2002
DOI: 10.1080/102538902900012369
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Brain Response to Social Stress in Rodents With c-fos Expression: A Review

Abstract: Social defeat is an important event in the life of many animals, and forms part of the process of social control. Adapting to social defeat is thus an intrinsic part of social "homeostasis", and mal-adaptation may have pathological sequelae. Experimental models of social defeat (e.g. inter-male aggression) have existed for many years. However, very few studies have investigated the changes in brain activity in male animals exposed to the social stress of being defeated by another conspecific male, and in all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
96
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 62 publications
7
96
0
4
Order By: Relevance
“…While open field exposure per se likely involves induction of a fear-like state due to the unfamiliar circumstances, the lack of a significant c-Fos increase may be due to insufficient intensity of this psychogenic stressor. Indeed, in other studies it has been shown that c-Fos is reliably increased in the CeC in response to a variety of psychological stressors (Pacak et al, 1995,Senba and Ueyama, 1997,Martinez et al, 2002,Rossi-George et al, 2005. Nonetheless, CeC activation by MeHg suggests engagement of neural substrates necessary for adaptational physiological and behavioral responses, and is consistent with the significant reduction in exploratory behavior observed in MeHg treated mice.…”
Section: Discussionsupporting
confidence: 69%
“…While open field exposure per se likely involves induction of a fear-like state due to the unfamiliar circumstances, the lack of a significant c-Fos increase may be due to insufficient intensity of this psychogenic stressor. Indeed, in other studies it has been shown that c-Fos is reliably increased in the CeC in response to a variety of psychological stressors (Pacak et al, 1995,Senba and Ueyama, 1997,Martinez et al, 2002,Rossi-George et al, 2005. Nonetheless, CeC activation by MeHg suggests engagement of neural substrates necessary for adaptational physiological and behavioral responses, and is consistent with the significant reduction in exploratory behavior observed in MeHg treated mice.…”
Section: Discussionsupporting
confidence: 69%
“…Social stress-induced alterations of gene expression in limbic areas are involved in long-term neuroadaptations and behavioral impairments (Martinez et al, 2002). Interestingly, a number of reports linked BDNF neurotransmission in the neuropathophysiology of psychiatric disorders in general (Balaratnasingam and Janca, 2012) and depression in particular (Duman and Monteggia, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the BNST is activated by acute stressors (Bonaz and Tache 1994;Campeau and Watson 1997;Kollack-Walker et al 1997;Martinez et al 1998Martinez et al , 2002, likely from excitatory glutamatergic and/or CRF-containing inputs from the amygdala, ventral subiculum and limbic cortices, and is essential for stress-induced learning (Bangasser et al 2005). Chronic stress, which is known to produce depressive-like symptoms such as anhedonia, elevates levels of CRF in the BNST (Chappell et al 1986;Stout et al 2000).…”
Section: Discussionmentioning
confidence: 99%